Teachers’ Quality and Secondary School Students’ Academic Performance in Islamic Studies in Ilorin, Nigeria - Ajidagba, U. A.; Abdur-Rafiu, Jamiu; Usman, Adisa Issa (NIU Journal of Social Sciences, 2018)
The development of any society is determined by the quality of its education and the quality of education is determined by the quality of teachers. Teachers’ quality, however, can be regarded as one of the vital academic determinants that have profound relationship with students’ academic performance in all levels of educational system in Nigeria. It is against this background that the study investigated the teachers’ quality and secondary school students’ academic performance in Islamic studies in Ilorin, Nigeria. 60 secondary schools were selected across the five Local Government Areas forming Ilorin Emirate, Kwara state. In all, 300 students were selected using simple random technique. Purposive sampling technique was employed in selecting 300 Islamic studies teachers for the study. Questionnaire was used to elicit information on teachers’ quality from the respondents, while May/June West African Examination Council, 2013 Objective Test was adapted to test SSII students’ academic performance in Islamic studies and a profoma for SSI students’ academic performance in Islamic studies was collected. The findings of the study revealed no significant relationship between teachers’ teaching approach, subject mastery and secondary school students’ academic performance in Islamic studies in Ilorin Emirate. However, significant relationship was recorded between teachers’ educational qualification, years of teaching experience and academic performance of secondary school students in Islamic studies in Ilorin Emirate. Necessary recommendations were made based on the findings of the study. Keywords: Teachers, Quality, Students, Academic, Performance